2020
DOI: 10.3390/diagnostics10060388
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Cardiac Morphological Alterations in a Pentylenetetrazol-Kindling Model of Epilepsy

Abstract: Epilepsy is a group of neurological disorders characterized by abnormal electrical activity in the central nervous system (CNS) and recurrent seizures representing the principal clinical manifestation. Sudden unexpected death in epilepsy (SUDEP) is the predominant cause of death in young epileptic patients. SUDEP patients displayed an increased cardiovascular (CV) risk, probably due to an impaired autonomic control of CV functions, but the underlying mechanisms need to be explored yet. Therefore, we aimed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Tissue samples obtained from rats exposed to the kindling model were determined with a 10% formaldehyde solution for use in histological examinations. After the detection process, routine tissue follow-up steps were applied to the tissues and embedded in paraffin to perform the paraffin blocks ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue samples obtained from rats exposed to the kindling model were determined with a 10% formaldehyde solution for use in histological examinations. After the detection process, routine tissue follow-up steps were applied to the tissues and embedded in paraffin to perform the paraffin blocks ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue sections (5 μm) were obtained from the paraffin blocks and then placed on polylysine-coated slices for morphological analysis. The prepared slides were left in the oven for a certain period using standard histological methods as described in Akyuz et al ( 10 ). Xylene and paraffin were removed and passed through a graded alcohol series and diluted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTZ injection was continued until seizure kindling was achieved, but never longer than 4 weeks. Seizure kindling was considered achieved when the animals showed a Score 4 or 5 after three consecutive injections of PTZ [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the immunoreactivity of Kir3.1 and muscarinic ACh receptor 2 (M2) was observed in the vagus nerve and heart tissue of epileptic rats (Akyuz, Doganyigit, et al., 2020). In addition, cardiac morphology studies performed in epileptic rats reported that the distance between the atria was found to be decreased, the overall heart weight was found to be increased, and a number of hemorrhagic areas were to be observed in the cardiac tissue (Akyuz, Polat, et al., 2020). Taken together, altered immunoreactivity of ACh‐associated Kir3.1 and M2 receptors on the heart and vagus nerve as well as the changing blood pressure and ECG findings (Figure 2) elucidate the mechanisms of cardiac pathologies that were associated with autonomic dysfunction in epilepsy.…”
Section: Cardiorespiratory Findingsmentioning
confidence: 99%